PERSONAL BRANDING KIAI POLITISI BERBASIS CIRCLE-C - Khotijah, Khotijah; Mundiri , Akmal (Managere: Indonesian Journal of Educational Management, 2020)
This paper present the Kiai in an era of disruption who is required to be involved in the world of politicians without having to reduce the counterproduction of a Kiai. This study uses the Library Research method which is based on the philosophy of postpositivism and emphasizes the ethnographic model which aims to describe cultural characteristics. Furthermore, the authors explain the implementation of the model in various disciplines. The result showed that Kiai Politicians who have great potential to bring pesantren's environment to the realm of politic's world without damaging the reputation of a Kiai himself. By this role as a politician, Kiai is required to be able to influence the community with a sincere spirit who adheres to Islamic law. This is where the role of a politician Kiai requires a circle-C formula in a Kiai Politician Personal Branding. Competency, able to improve the society's paradigm towards politician Kiai. Connectivity, the strategic rule in media education, is better monitored. Creatifity, understanding passion as an action, and Contribution is being able to control the reputation of the keys that have been built.